EFEKTIVITAS MEDIA SOSIAL FACEBOOK DALAM PELAYANAN INFORMASI DI BAGIAN HUMAS RUMAH SAKIT UMUM DAERAH KABUPATEN KLUNGKUNG - Rai Tirtawati, Anak Agung; Ayu Yuliawati, Nyoman (Jurnal Kajian Ilmu Komunikasi, 2021)
The information technology development in the age of globalization, social networking has become a trend among people, one of them is facebook. facebook has also been used for political, business and even integrated into the information service system at a hospital, the Klungkung District Hospital. This research was conducted at the Regional General Hospital of Klungkung Regency.Based on visitor data from March 23 to 28, 2020 amounted to 1191, using the Slovin formula found 397 samples / respondents. Researchers use data analysis methods using qualitative descriptive analysis and qualitative approaches to data collection using observation techniques, questionnaires, and documentation in data collection. From the results of data analysis and discussion that have been described, the conclusion can be drawn is after conducting research using a questionnaire that has been given to patient respondents or a companion / patients escortedtotalling 397 questionnaires, showing that facebook social media is very effective in information services at the public relations section of the Regional General Hospital of Klungkung Regency